Cancer-specific senescence signature promotes malignant phenotypes and immunotherapy resistance in colorectal cancer - Wang, Wei; Ling, Fengyu; Huang, Dong; Luo, Guomin; Duan, Bixia (Frontiers in Immunology, 2025)
BackgroundWhile cellular senescence in colorectal cancer (CRC) exhibits strong correlations with immunotherapy response and clinical prognosis, its mechanistic basis remains elusive, and validated predictive biomarkers are currently unavailable.MethodsIn this study, we integrated single-cell and bulk transcriptomic data to establish a cancer-specific senescence signature (CSS). Systematic biological characterization revealed that the CSS remodels the tumor microenvironment (TME), primarily through perturbed immune cell infiltration and CD8+ T-cell dysfunction. Functional validation via shRNA-mediated CD24 knockdown in HCT116 cells was corroborated by Western blot and flow cytometry. CD24 ablation’s effects on malignant phenotypes were assessed using colony formation, Transwell invasion, wound healing, and proliferation/apoptosis assays (Ki67/Annexin V/TUNEL). CSS-mediated CD8+ T-cell regulation was investigated using palbociclib-induced senescence models (HCT116/SW480). Potential senescence-targeting compounds were identified via the Cancer Therapeutics Response Portal (CTRP) and PRISM databases.ResultsOur analyses validated the CSS as both a prognostic biomarker and immunotherapy predictor in CRC. CSS-high tumors displayed diminished cytotoxic T-cell infiltration and impaired CD8+ effector functions (reduced IFN-γ/granzyme B production), while CSS-low tumors showed enhanced T-cell activity. Mechanistic investigations revealed CSS-mediated immunosuppression via MHC class I dysregulation, compromising tumor antigen recognition. Genetic CD24 inhibition suppressed proliferation, migration/invasion and triggered apoptosis. Computational screening identified afatinib as a potent CSS-targeting agent, with in vitro studies confirming selective senescent cell growth inhibition through proliferation blockage and apoptosis induction. Notably, CSS-high status predicted immunotherapy resistance.ConclusionCollectively, CSS drives tumor aggressiveness and independently predicts unfavorable survival outcomes and immunotherapy resistance in CRC. Notably, afatinib targeting of CSS selectively eliminated senescent cells via apoptosis while inhibiting tumor growth, highlighting its therapeutic potential for CSS-high malignancies.